2018
DOI: 10.1021/jacs.8b09440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Scale Ligand Effects in Small Gold–Thiolate Nanoclusters

Abstract: Because of the small size and large surface area of thiolate-protected Au nanoclusters (NCs), the protecting ligands are expected to play a substantial role in modulating the structure and properties, particularly in the solution phase. However, little is known on how thiolate ligands explicitly modulate the structural properties of the NCs at atomic level, even though this information is critical for predicting the performance of Au NCs in application settings including as a catalyst interacting with small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 32 publications
0
79
2
2
Order By: Relevance
“…Zhang examined the interaction of solvent and superatoms, 144,145 which is often overlooked due to the difficulty of characterization in solution. A slight change of geometric and electronic structure of [Ag 44 (p-MBA) 30 ] 4in solution was monitored by XAS.…”
Section: Condensed Phase Methodsmentioning
confidence: 99%
“…Zhang examined the interaction of solvent and superatoms, 144,145 which is often overlooked due to the difficulty of characterization in solution. A slight change of geometric and electronic structure of [Ag 44 (p-MBA) 30 ] 4in solution was monitored by XAS.…”
Section: Condensed Phase Methodsmentioning
confidence: 99%
“…[40] Wavelet transformation (WT) provides a complementary method to FT-EXAFS by combining radial distance distribution and k-space in the form of a 2D-contour plot, where the k-space shows the oscillations caused by the interactions between a target atom and backscattering atoms. [41][42][43] As an example, Figure 3B,C show the FT-EXAFS and WT-EXAFS of silver nanoclusters protected Pd K-edge C) X-ray absorption near-edge structure (XANES) and D) Fourier-transformation-extended X-ray absorption fine structure (FT-EXAFS) spectra of 0.4 wt%-Pd(NH 3 ) 4 Cl 2 /USY measured every 0.6 min in a 5% H 2 flow at room temperature. Reproduced with permission.…”
Section: X-ray Absorption Spectroscopymentioning
confidence: 99%
“…[ 40 ] Wavelet transformation (WT) provides a complementary method to FT‐EXAFS by combining radial distance distribution and k‐space in the form of a 2D‐contour plot, where the k‐space shows the oscillations caused by the interactions between a target atom and backscattering atoms. [ 41–43 ] As an example, Figure 3B,C show the FT‐EXAFS and WT‐EXAFS of silver nanoclusters protected by tiopronin, respectively. [ 41 ] In the FT‐EXAFS spectrum, only two scattering paths were assigned corresponding to AgS and AgAg shells, while the peak above 3 Å could not be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Because these SRs have substantially different functional groups (Scheme S1 †), the resulting Au n (SR) m clusters have different chemical compositions and geometrical structures. 28,29 For example, when PET is used as the ligand, Au n (PET) m clusters, such as [Au 25 (PET) 18 ] − , [Au 38 (PET) 24 ] 0 , [Au 52 (PET) 32 ] 0 , [Au 144 (PET) 60 ] 0 , and [Au 329 (PET) 84 ] 0 , are formed, whereas, in the case of TBBT, Au n (TBBT) m clusters, such as [Au 28 (TBBT) 20 ] 0 , [Au 36 (TBBT) 24 ] 0 , [Au 52 (TBBT) 32 ] 0 , [Au 133 (TBBT) 52 ] 0 , and [Au 279 (TBBT) 84 ] 0 , are generated. The numbers of gold atoms and ligands are the same in [Au 52 (PET) 32 ] 0 and [Au 52 (TBBT) 32 ] 0 , but their framework structures are significantly different.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the chemical composition of the cluster, the stability, electronic structure, and functions of Au n (SR) m clusters change depending on the functional-group structure of the ligand. 9,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] For example, it has been demonstrated that properties of Au 25 (SR) 18 , such as the stability in solution, reducibility, dissociation pattern under laser irradiation, quantum yield of photoluminescence, and catalytic activity, along with other properties, differ depending on the functional-group structure of the ligand. Therefore, the selection of the ligand functional group is essential in the functionalization of Au n (SR) m clusters.…”
Section: Introductionmentioning
confidence: 99%